Докажите тождество: (х+у)2 -(х-у)2 =4ху.

maximorlov04 maximorlov04    2   06.05.2019 22:14    1

Ответы
alla50011 alla50011  09.06.2020 14:07

Объяснение:

(х+у)2 -(х-у)2 =4ху

х²+2ху+у²-(х²-2ху+у²)=4ху

х²+2ху+у²-х²+2ху-у²+4ху

(Зачёркиваешь х²-х² у² -у², так как они взаимно уничтожаются)⇒

2ху+2ху=4ху

4ху=4ху

ПОКАЗАТЬ ОТВЕТЫ
Parf21 Parf21  09.06.2020 14:07

Объяснение:

(х+у)²-(х-у)²=x²+2xy+y²-(x²-2xy+y²)=x²+2xy+y²-x²+2xy-y²=2xy+2xy=4xy

4xy=4xy

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра